Analisis Pengaruh Motivasi Kerja terhadap Jumlah Penjualan (Studi Kasus: Pabrik Kerupuk Lina, Bandung) - ., Yulianti; Azis, Norman; Azis, Norman (Zenit, 2013)
Lina Cracker Factory is a company engaged in the manufacture and marketing of traditional crackers made from tapioca flour. This company is located on Babakan Loa 28, Bandung. The company is facing problems of declining sales over the last few years. This  study aimed to explore the influence of sales department workers’ motivation to total sales made by the sales department workers. Worker motivation variables as independent variables drawn from the theory of Abraham Maslow and sales data crackers will be the dependent variable. Data was collected through interviews with company owner, interviews with sales department workers and questionnaires distributed to 35 sales department workers. Through the processing of the questionnaires showed that sales department  workers in Lina Cracker Factory lacked motivation at work. By using Multiple Linear Regression method, it is found that there are 5 variables that significantly affect the sales department workers’ motivation. There is a strong  positive relationship between sales department workers’ motivation and total traditional crackers sales, with correlation coefficients value 0.851. The multiple linear regression model can explain 72.5% variance of total traditional crackers sales. To increase total traditional crackers sales, the company can do several things namely appropriate reward performance, superior being friendly to all employees, provide wheel a sworking tools for all sales department workers, and provide adequate housing facilities.  Keywords: Motivation, sales, Multiple Linear Regression